IMPACT OF MACROECONOMIC FACTORS ON INDUSTRIAL PRODUCTION IN GHANA - Patrick Enu; Edmond Hagan; Prudence Attah-Obeng (European Scientific Journal, ESJ, 2013)
The article looks at the impact of macroeconomic indicators on industrial production in Ghana. The ordinary least squares estimation technique is utilized given the sample size of 21 due to the unavailability of data. The study identified real petroleum prices (-), real exchange rate (-), import of goods and services (+) and government spending (+) as the key macroeconomic factors that influence industrial production in Ghana. Based on the findings, we recommend that the government of Ghana should continue to stabilize the macroeconomic environment of Ghana in order to achieve industrial growth and development.